Resposta imune induzida por antígenos de Mycoplasma hyopneumoniae avaliados como vacina de DNA ou subunidade recombinante. - Galli, Vanessa (2011)
Mycoplasma hyopneumoniae is the causative agent of Porcine Enzootic Pneumonia (PEP), one of the most common respiratory diseases in swine industry worldwide. Commercially available vaccines are inactivated whole-cell preparations (bacterin), which provide only partial protection and do not prevent microorganism colonization. In this context, it is necessary to search new alternatives prophylaxis. Potential antigens are being tested in different vaccination strategies; however none was more efficient than commercial bacterins for PEP control. This work aimed the production and evaluation of antigenicity and immunogenicity of M. hyopneumoniae antigens delivered as naked DNA and/or recombinant subunit vaccines, aiming the development of a vaccine against PEP. Recombinant subunit vaccines were obtained by the expression of eleven M. hyopneumoniae recombinant proteins in E. coli and purification by affinity chromatography, whereas the DNA vaccines were obtained by cloning four M. hyopneumoniae genes in pcDNA3 vector. Recombinant proteins antigenicity was verified against convalescent pig serum. The humoral and cellular immune response elicited by these vaccines was evaluated in mice immunized intramuscularly. All recombinant proteins evaluated were recognized by convalescent pig serum, in ELISA and/or Western blot assay, especially MHP0418, indicating that they are expressed during disease. These recombinant proteins, as well as P37, P42, P46 and P95 showed immunogenic capacity, eliciting both Th1 and Th2 immune response. The P37, P42, P46 and P95, and the DNA vaccine pcDNa3/P46 were also able to elicit INFγ expression, the cytokine associated with cellular immune response, and decrease TNFα and IL1 expression, both associated with pig lesions, during M. hyopneumoniae infeccion, suggesting their potencial as candidate vaccines. The immunization strategy using proteins combinated potencialized the immune response, and the MHP0443 and MHP0372 proteins were the main responsable for the Mix1 and Mix2 immunogenicity, respectivally. Moreover, MHP0107, MHP0418 and MHP0372 elicited antibodies that react against proteins from M. hyopneumoniae strains 7448, 4722 and J, and did not show cross reaction with M. hyohinis and M. flocculare. Thus, these proteins could be used in imunodiagnosis assay.